2018
DOI: 10.1038/s41467-018-07174-1
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Tie2 is a tumor vascular response biomarker for VEGF inhibitors in metastatic colorectal cancer

Abstract: Oncological use of anti-angiogenic VEGF inhibitors has been limited by the lack of informative biomarkers. Previously we reported circulating Tie2 as a vascular response biomarker for bevacizumab-treated ovarian cancer patients. Using advanced MRI and circulating biomarkers we have extended these findings in metastatic colorectal cancer (n = 70). Bevacizumab (10 mg/kg) was administered to elicit a biomarker response, followed by FOLFOX6-bevacizumab until disease progression. Bevacizumab induced a correlation b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 50 publications
0
46
1
Order By: Relevance
“…Ang-2 is known to be produced by cancer cells and plays important roles in regulating tumor angiogenesis [27,28,30]; additionally, it has been reported as a potential prognostic biomarker for certain types of cancers, including HCC [14,[24][25][26]. Several studies have reported high circulating (serum or plasma) Ang-2 levels as a predictor of tumor invasiveness or as a diagnostic biomarker of HCC [14,31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Ang-2 is known to be produced by cancer cells and plays important roles in regulating tumor angiogenesis [27,28,30]; additionally, it has been reported as a potential prognostic biomarker for certain types of cancers, including HCC [14,[24][25][26]. Several studies have reported high circulating (serum or plasma) Ang-2 levels as a predictor of tumor invasiveness or as a diagnostic biomarker of HCC [14,31,32].…”
Section: Discussionmentioning
confidence: 99%
“…For example, upregulated delta-like protein 3 (DLL3) overexpression is an independent prognostic predictor for endometrial cancer and could be a potential and novel tumor marker for the early diagnosis of endometrial cancer [10]. Plasma Tie2 is a tumor vascular response biomarker for vascular endothelial growth factor (VEGF) inhibitors in metastatic colorectal cancer [11]. Nevertheless, researchers found that rather than single gene biomarkers, gene signatures that include several genes can be good evidence for the prognosis and survival of tumors.…”
Section: Introductionmentioning
confidence: 99%
“…The trajectory of VEGF‐R2, however, has not been investigated. We and others have reported on the clinical significance of angiopoietin pathway components (Ang1, Ang2 and Tie2) in patients receiving the VEGF inhibitor bevacizumab treatment for ovarian and colorectal cancer . On the basis of these previous studies, VEGF‐R2, VEGF‐A, Ang1 and Tie2 were selected for evaluation in this study.…”
Section: Introductionmentioning
confidence: 99%